"Efl teaching methods applied in online classes on the major in pedagogy of national and foreign languages" - Benavides Pruna, Miguel Angel (2022)
There are many teaching methods in second language acquisition and each one is different from the other. The main objective of this study was to report which teaching methods teachers are applying through an English online class. To obtain data, a qualitative research was applied. A bottom-up approach was applied to analyze the data. The instrument used in the study was an interview administered to twelve English students from the Technique University of Cotopaxi. The results of the study revealed that the Audio-Lingual Method [ALM], Direct Method [DM], Communicative Language Teaching and Oral Approach or Situational Language Teaching [SLT] were the main methods found in the foreign language classrooms studied. Regarding the teaching method, activities used in class were varied, which means the teachers do not use repetitive activities to develop the class, so that they are not limited. In addition, the online lessons were more complicated and the teacher implemented more activities to help students get the objective of the class. These activities provided and enhanced the students with spaces to interact with each other. One of the ways to improve the educational reality in the English area is understand the form of teaching that is applied in the classroom, in the other hand, to know the methods of teaching English as a second language, and from these results, get the educational authorities to establish the strategies that they could contribute to improve this situation. In the case of the major in Pedagogy of National and Foreign Languages, there is no empirical evidence on studies related to determining the type of methodological strategies and teaching methods that are applied during the professional training of students in this career, this is important to know the starting point for future decisions that could be adopted.